Obtenção de pontos quânticos de carbono a partir do lodo de esgoto doméstico - Rossi, Bruno Leonel (2019)
Sewage sludge, produced daily and inherent to urban development, show problems with destination untill today challenging. It destination still show (presents) palliative solutions, generally adopted as final destination the landfills, and it can be used, in a restrict way, in agriculture. The synthesis of Carbon Quantum Dots (CQDs) from sewage slugde is a new alternative to exploitation of the stock of organic material presente in the slugde. CQDs applications have been reported as promising in biosensors, chemical analyses, bioimages, drug release, photocatalysis, optoeletronic devices (LED and OLED) and solar cells. This presente work looked for a new alternative to the final destination of the sewage sludge, using principles of green chemistry, and in order to utilize its intrinsic carbon stock, using it (them) as raw material in the production of CQDs. It was used two synthesis routes: I) by microwaves, this was chosen because it is pointed as an advanced tool in synthesis processes that require heat, being obteined CQDs with Quantum Yield (QY) equal to 2,59%.; and II) by hydrothermal treatment in autoclave, being in this process obtained CQDs with QY equal to 2,67%. The synthesis by the method (I) reduced by 20 times the time of the exposure to the heat to the production of the CQDs, when compered to the method (II). The photoluminescence spectroscopy analysis showed that the CDQs excitation λmax was at 360 nm and caused a λmax emission at 430 nm. The CQDs obtained by microwave synthesis showed sizes of 9,69 ± 2,64 nm, while the CQDs obtained by hydrothermal treatment had a diameter of 10,917 ± 2,69 nm. Other characterization methods were used, such as TG/DTA, EGA, FTIR, besides the UV-vis absorption spectroscopy. These characterizations allowed to suggest that the prepared CQDs are nucleus compound mostly of carbon, and show functional groups containing súlfur, nitrogen and oxygen in its structure. The caractherization techniques allow to suggest still some distinctions in the formation of CQDs, caused by the synthetic routes approached. The CQDs showed a dacay time of of luminescence relative to fluorescente compounds. He luminescence presented by these materials was equivalent to the quantum carbono points reported in the literature, even if it was not used a passivator/oxidant agente or purification processes of the obtained materials.